Reviewing Identity: Vojvodina of the Ninth Decade of the Past Century - Marković, Saša S. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The paper represents a consideration of attitudes related to the national-political status of Vojvodina after the death of Josip Broz, during the (re)affirmation of the constitutional and national identity of the socialist Yugoslav federation and its constituent elements. Relying on the existing continuity of discussions about the position of Vojvodina in the Republic of Serbia and the Yugoslav Federation, temporarily interrupted due to the honoring of the personality and work of Comrade Tito, the transition process, which increasingly turned into a process of disintegration of the joint state, testifies to the increasing number of contradictions regarding the future of the status of AP Vojvodina. Arising from ambivalent motives, they soon transformed into uncompromising antagonisms that persistently insisted on their own orthodoxy at the cost of a decisive conflict. In such circumstances, all interested parties ignored the fact of an overly cumbersome and bureaucratized party apparatus, and thus the state apparatus, which had long since lost any foothold in the political will of the population. For this reason, the massing of support, in one moment, became a decisive moment of prestige that led to the final political triumph. The accompanying populist manifestations decisively influenced the specific development of democratic pluralism, which intended to make a departure from the compromised ideology of the Yugoslav federation.
Keywords: Vojvodina; identity; nationalism; reform; conflict; policy